Postpartum Pulmonary Hypertension Masquerading as Submassive Pulmonary Embolism: A Case Report and a Literature Review - Mahmood Mubasher (14570517) (2020)
Postpartum pulmonary hypertension (PPPHT) is an extremely rare disorder, with few reported cases. Late diagnosis and treatment are associated with significant morbidity and mortality. We present an 18-year-old female patient who presented four-week postpartum with a typical submissive pulmonary embolism picture subsequently diagnosed as postpartum pulmonary hypertension. The patient had an excellent response to treatment, with a dramatic improvement in her functional status. The authors aim to urge physicians to keep this rare disorder in mind as timely and accurate diagnosis is crucial for management—additionally, the importance of counseling patients about the imminent risks associated with planned future pregnancies.  Other information  Published in: Case Reports in Pulmonology License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1155/2020/8899562